Economic evaluation of encorafenib with cetuximab in patients with BRAF V600E-mutant metastatic colorectal cancer in France: a cost-effectiveness analysis using data from the BEACON CRC randomised controlled trial - David Malka; Philippe Laramée; Mondher Toumi; Jean-Baptiste Trouiller; Bérengère Macabeo; Andrew Poll; Dan Howard; Andy Buckland; Marine Sivignon; Emilie Clay; Emmanuelle Samalin (BMJ Open)
Objective The BEACON CRC randomised controlled trial (NCT02928224) in BRAF-mutant metastatic colorectal cancer (mCRC) patients showed improved overall survival for the combination treatment of encorafenib (BRAF inhibitor) with cetuximab (EGFR inhibitor) compared with cetuximab with chemotherapy (FOLFIRI (folinic acid, fluorouracil and irinotecan) or irinotecan). We aimed to evaluate the cost-effectiveness of encorafenib with cetuximab in adult patients with BRAF-mutant mCRC after prior systemic therapy, from the perspective of the French healthcare system.Design A partitioned survival analysis model was developed to assess the cost-effectiveness of encorafenib with cetuximab using data from BEACON CRC (encorafenib with cetuximab and cetuximab with FOLFIRI or irinotecan). For two further comparator treatments (FOLFIRI alone and bevacizumab with FOLFIRI), a systemic literature review identified appropriate clinical trial data for indirect comparison. Piecewise modelling extrapolation was used to fulfil a lifetime horizon in the model. A discount rate of 2.5% was used. Treatment-emergent adverse events ≥grade 3 with an incidence of ≥2% were included, as well as relative dose intensity and utility values.Outcome measures The effectiveness outcomes of the model were expressed in terms of incremental life years gained and incremental quality-adjusted life years (QALY) gained. The cost-effectiveness of encorafenib with cetuximab was assessed using the incremental cost-effectiveness ratio (ICER). Results were presented probabilistically to account for parametric uncertainty. Deterministic and scenario analyses were conducted.Results The ICER for encorafenib with cetuximab versus cetuximab with FOLFIRI or irinotecan, FOLFIRI alone and bevacizumab with FOLFIRI was €69 823/QALY, €70 421/QALY and €72 336/QALY, respectively. Encorafenib with cetuximab was considered cost-effective compared with the three comparators at a willingness to pay threshold of €90 000/QALY, with probabilities of being cost-effective of 89.8%, 98.2% and 86.4%, respectively.Conclusions This analysis showed encorafenib with cetuximab to be a cost-effective treatment in mCRC patients with a BRAF V600E mutation.